Surfactant protein D is a causal risk factor for COPD: results of Mendelian randomisation. Issue 5 (30th November 2017) - Obeidat, Ma'en; Li, Xuan; Burgess, Stephen; Zhou, Guohai; Fishbane, Nick; Hansel, Nadia N.; Bossé, Yohan; Joubert, Philippe; Hao, Ke; Nickle, David C.; van den Berge, Maarten; Timens, Wim; et al.
Surfactant protein D (SP-D) is produced primarily in the lung and is involved in regulating pulmonary surfactants, lipid homeostasis and innate immunity. Circulating SP-D levels in blood are associated with chronic obstructive pulmonary disease (COPD), although causality remains elusive. In 4061 subjects with COPD, we identified genetic variants associated with serum SP-D levels. We then determined whether these variants affected lung tissue gene expression in 1037 individuals. A Mendelian randomisation framework was then applied, whereby serum SP-D-associated variants were tested for association with COPD risk in 11 157 cases and 36 699 controls and with 11 years decline of lung function in the 4061 individuals. Three regions on chromosomes 6 (human leukocyte antigen region), 10 ( SFTPD gene) and 16 ( ATP2C2 gene) were associated with serum SP-D levels at genome-wide significance. In Mendelian randomisation analyses, variants associated with increased serum SP-D levels decreased the risk of COPD (estimate −0.19, p=6.46×10 −03 ) and slowed the lung function decline (estimate=0.0038, p=7.68×10 −3 ). Leveraging genetic variation effect on protein, lung gene expression and disease phenotypes provided novel insights into SP-D biology and established a causal link between increased SP-D levels and protection against COPD risk and progression. SP-D represents a very promising biomarker and therapeutic target for COPD. Surfactant protein D is a causal risk factor for COPD http://ow.ly/n1OG30eUQlf